Diver operated video most accurately detects the impacts of fishing within periodically harvested closures - Goetze, J.; Jupiter, S.; Langlois, T.; Wilson, S.; Harvey, Euan; Bond, T.; Naisilisili, W. (Elsevier, 2015)
Periodically harvested closures (PHCs) have become the most common form of spatial management in Melanesia. Despite their popularity, their effectiveness to sustain local fish stocks remains largely unknown. Here we test the ability of non-destructive sampling techniques to detect the impacts of fishing in a PHC where harvest catch data provide an impact of known magnitude. We compared the ability of three commonly used techniques (underwater visual census, UVC; diver operated stereo-video, stereo-DOV; and baited remote underwater stereo-video, stereo-BRUV) to detect the impact of a harvest on fish assemblages within a PHC in Fiji. Thetechnique stereo-DOV recorded a significant decrease in harvested individuals at both the assemblage and species level (primarily herbivorous species). The technique stereo-BRUV also recorded an impact at the assemblage level, but only for carnivorous fishes, which were less numerous in the catch. UVC did not detect an impact of the harvest at the assemblage or species level. We conclude that stereo-DOV is the most suitable technique for detecting the impactsof harvests and monitoring the effectiveness of PHCs as a fisheries management strategy, especially in areas where herbivorous fish are targeted. However, stereo-BRUV may be more appropriate where strong gradients in the abundance of carnivorous species or behavioural responses to divers are expected.